Loss probabilities for messages with redundant packets feeding a finite buffer. - Altman, E. (IEEE Journal on selected areas in communications)
The purpose of this paper is to obtain the distribution of the number of lost packets within a sequence of n consecutive packet arrivals into a finite buffer M/M/1 queue. We obtain explicit expressions for the multidimensional generating function of these probabilities based on a recursive scheme introduced by Cidon et al. (1993). We then analyze the loss probabilities of a whole message, and analyze the effect of adding redundant packets. We show that in both heavy traffic as well as in light traffic conditions, adding redundant packets results in decreasing the message loss probabilities